2019
DOI: 10.1021/jacs.8b12964
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Inspired Strand-Exchange for Switchable PMMA-Based Supramolecular Morphologies

Abstract: Inspired by nanotechnologies based on DNA strand displacement, herein we demonstrate that synthetic helical strand exchange can be achieved through tuning of poly(methyl methacrylate) (PMMA) triple-helix stereocomplexes. To evaluate the utility and robustness of helical strand exchange, stereoregular PMMA/polyethylene glycol (PEG) block copolymers capable of undergoing crystallization driven self-assembly via stereocomplex formation were prepared. Micelles with spherical or wormlike morphologies were formed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Recent advances to achieve two orthogonal stereoselective CAPs in one pot resulted in the in situ synthesis and fabrication of stereocomplexed poly­(MMA). Stereocomplexed poly­(MMA) exists as a triple-helix structure (a double helix of isotactic poly­(MMA) surrounded by a single helix of syndiotactic poly­(MMA)) formed through van der Waals interactions. This supramolecular structure exhibits a significantly higher crystallinity and T m when compared to its individual stereoregular components that have been exploited for a variety of applications. ,, Chen and co-workers recently used a mixture of C 2 - and C s -symmetric zirconocene bis­(ester enolate) catalysts to combine both synthesis and fabrication of stereocomplexed poly­(MMA) into a rapid single-step method . Polymer chain exchange between reactive centers was not evident, and real-time dynamic light scattering indicated that efficient stereocomplexation had occurred in situ as polymer chains were growing.…”
Section: Coordination–addition Polymerizationmentioning
confidence: 99%
“…Recent advances to achieve two orthogonal stereoselective CAPs in one pot resulted in the in situ synthesis and fabrication of stereocomplexed poly­(MMA). Stereocomplexed poly­(MMA) exists as a triple-helix structure (a double helix of isotactic poly­(MMA) surrounded by a single helix of syndiotactic poly­(MMA)) formed through van der Waals interactions. This supramolecular structure exhibits a significantly higher crystallinity and T m when compared to its individual stereoregular components that have been exploited for a variety of applications. ,, Chen and co-workers recently used a mixture of C 2 - and C s -symmetric zirconocene bis­(ester enolate) catalysts to combine both synthesis and fabrication of stereocomplexed poly­(MMA) into a rapid single-step method . Polymer chain exchange between reactive centers was not evident, and real-time dynamic light scattering indicated that efficient stereocomplexation had occurred in situ as polymer chains were growing.…”
Section: Coordination–addition Polymerizationmentioning
confidence: 99%
“…[15][16][17][18][19] Amphiphilic block copolymers are widely being used as key building blocks to create a variety of nanostructured materials such as micelles, vesicles, sheets, and tubes. [20][21][22][23] The morphological behavior would be controlled by altering the polymer properties such as hydrophilicity, hydrophobicity, flexibility, volume fraction, and composition. Significant efforts have been made to generate well-defined amphiphilic block copolymers that allow for precise control over the size and shape of their self-assembled structures.…”
Section: Introductionmentioning
confidence: 99%
“…Although atactic polymethyl methacrylate (PMMA) does not form any specific structure, syndiotactic PMMA forms a helical structure, with 1 nm inner diameter and 2.3 nm outer diameter, in organic solvents. The syndiotactic PMMA encapsulates isotactic PMMA and functional molecules in their helical cavity . In this work, we report the preparation of a novel block copolymer consisting of syndiotactic PMMA and polymethacrylate‐functionalized POSS (PMAPOSS), designated as ( st ‐PMMA‐ b ‐PMAPOSS), and the encapsulation behavior of the st‐ PMMA segments in the block copolymer.…”
Section: Introductionmentioning
confidence: 99%